Efficacy of Chitosan as Clarifying Agent to Physico-chemical and Organoleptic Attributes of Pineapple Juice during Clarification - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2020)
Turbidity is a major obstacle in preservation of fruit juice and concentrate. This phenomenon is also not acceptable in handling and distribution of commercial beverage. Fruit juice is a complex of soluble and insoluble multi components in suspension. Clarification is a crucial step to remove pectin, carbohydrate, metal ion as well as solid particles existing in fruit juice to achieve a clear and stable status. As a natural abundant polymer, chitosan has been proven as an alternative approach for juice clarification with diversified manipulations in appropriate cost. Our study focused on the feasibility of chitosan as clarifying agent to physico-chemical and organoleptic properties of pineapple juice during clarification. Different concentrations of chitosan (0.05, 0.075, 0.1, 0.125, 0.15%) and agitation speeds (40, 60, 80, 100, 120 rpm) have been investigated fruit juice to evaluate turbidity (NTU), viscosity (cP), total soluble solid (oBrix), total phenolic (mg GAE/g), flavonoid (mg GE/g) and sensory score after clarification. Our results revealed that 0.125% chitosan; agitation speed 80 rpm were adequate and efficient for juice clarification. As being nontoxic and biodegaradable, chitosan could be effectively utilized as an alternative agent for refining of fruit juice.Keywords: Pineapple juice, Clarification, Chitosan, Turbidity, Viscosity, Total soluble solid, Total phenolic, Flavonoid, Sensory score.